“Deshidratacion del sacha culantro (eryngium foetidum L.), por flujo de aire caliente” - Heredia Baca, Jensen Auseberto (2002)
The leaves give Sacha Coriander they are characterized by their wide, jagged form, and with thorny termination, give characteristic strong scent, give where exactly their name comes; this grass grows naturally in the shady heavy and humid lands near the cultivated areas. This product has meant for sorne countries an interesting source he/she gj~ revenues for effect he/she gives exports in fresh, because its consumption has been increased mainly among the population foreigner. In the tace of the possibility he/she gives to place this product in the market it is that he/she is carried out this work as part b-eLshe _giv~cs_ª-,n investigation in which you can determine the appropriate parameters he/she give§ temperature, speed he/she gives_ air, and through later studies he/she gives storage and commercialization to give the farmers an alternative he/she gives to have in associate plantations that can increase their revenues. The sacha coriander is used in the traditional medicine to combat the fevers and colds, vomits, diarrhea and in Jamaica for the colds and convulsions. The objectives of the present work were to determine a processing of suitable drying, in function to the temperature and velocity of the drying air, using sensorial evaluation of the obtained product and to determine the coefficients of diffusion of the present water in the leaves during the drying. The experimental part of the present work was developed in the Laboratory of Engineering and Projects of the National University of San Martin-Tarapoto. The tests were made in a convective dryer of laboratory with variable velocity and temperature of the drying air. Originating leaves of sacha-culantro of the small village of the Las Palmas were used, district of Banda de Shilcayo, department of San Martín. In the sensorial analysis it could notice that the highest values were obtained when the drying was made to the smaller temperature (40ºC), being less well-known the influence of air velocity. As far as the coefficient of diffusion of water, its value is increased from 3.04x10-11 m2/s to 17.00x10-11 m2/s when the temperature is increased of 40ºC to 60ºC. Water diffusion coefficients was determined fitting the Fick model for infinite slab to the experimental values, using a computar program, were close to the ranges reported in literature.